Mechanical Bowel Obstruction Caused by Incarcerated Left Amyand’s Hernia with Acute Appendicitis in Children - Abdul Hafiz, Muhammad Zaki; Jon Efendi; Budi Pratama Arnofyan (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Amyand’s hernia is rare condition defined as the inclusion of the appendixin an ingunal hernia sac, It is an uncommon and rare condition estimatedto be found in approximately 1 % of hernia. However, in just 0.08 %, thecondition is complicated by an acute appendicitis. It may present as atender inguinal or inguinoscrotal swelling. In patients presenting amyand’shernia with mechanical bowel obstruction, signs of acute appendicitis maynot be initially recognized. This was the case while our patient was insurgery, as signs suggestive of acute appendicitis were discovered and thepatient received appendectomy and herniotomy. Presently, We report a caseof Amyand’s hernia in a 9-month-old male, who presented as a left-sidedcongenital hernia with distended abdominal and pain in the left groin. Heunderwent appendectomy and herniotomy, which revealed that the herniasac containing elongated inflamed appendix appeared with some adhesionsto sac, lying in the inguinal canal.